FACTORS AFFECTING THE REPURCHASE INTENTION OF E-COMMERCE CUSTOMERS IN SHARING ECONOMY ACTIVITIES - Warniancy Ariesty; Ridho Bramulya Ikhsan (Journal of Business Studies and Management Review, 2021)
The sharing economy is a peer-to-peer activity in which people can obtain, provide, or share access to goods and service facilitated by a community-based online platform. However, transaction activities in e-commerce platforms frequently result in a slew of issues, including a lack of security for customer privacy data, fraud, and other risks that reduce consumers' willingness to make repeat purchases in e-commerce. The purpose of this study was to determine the factors that affect repurchase intentions, such as information quality, transaction security, and trust. Quantitative methods are used to solve the hypothesis. The research data was collected employing a questionnaire distributed to 160 customers who had shopped on the e-commerce platform. Questionnaire data were analyzed using PLS-SEM. The results indicate that the quality of information and transaction security has a positive and significant effect on trust, and trust has a positive and significant impact on repurchase intentions in e-commerce